A multicentre analytical comparison study of inter-reader and inter-assay agreement of four programmed death-ligand 1 immunohistochemistry assays for scoring in triple-negative breast cancer - Noske, Aurelia; Ammann, Johannes Ulrich; Wagner, Daniel-Christoph; Denkert, Carsten; Lebeau, Annette; Sinn, Peter; Kreipe, Hans H.; Sommer, Ulrich; Baretton, Gustavo Bruno; Steiger, Katja; Kiechle, Marion; Hieke-Schulz, Stefanie; et al. (Histopathology, 2021)
Aims Studies in various cancer types have demonstrated discordance between results from different programmed death-ligand 1 (PD-L1) assays. Here, we compare the reproducibility and analytical concordance of four clinically developed assays for assessing PD-L1-positivity in tumour-infiltrating immune cells in the tumour area (PD-L1-IC-positivity) in triple-negative breast cancer (TNBC). Methods and results Primary TNBC resection specimens (n = 30) were selected based on their PD-L1-IC-positivity per VENTANA SP142 (<1%: 15 cases; 1-5%: seven cases; >5%: eight cases). Serial histological sections were stained for PD-L1 using VENTANA SP142, VENTANA SP263, DAKO 22C3 and DAKO 28-8. PD-L1-IC-positivity and tumour cell expression (≥1 versus <1%) were scored by trained readers from seven sites using online virtual microscopy. The adjusted mean of PD-L1-IC-positivity for SP263 (7.8%) was significantly higher than those for the other three assays (3.7-4.9%). Differences in adjusted means were statistically significant between SP263 and the other three assays (P < 0.0001) but not between the three remaining assays when excluding SP263 (P = 0.0961-0.6522). Intra-class correlation coefficients revealed moderate-to-strong inter-reader agreement for each assay (0.460-0.805) and poor-to-strong inter-assay agreement for each reader (0.298-0.678) on PD-L1-IC-positivity. Conclusions In this first multicentre study of different PD-L1 assays in TNBC, we show that PD-L1-IC-positivity for SP142, 22C3 and 28-8 was reproducible and analytically concordant, indicating that these three assays may be analytically interchangeable. The relevance of the higher PD-L1-IC-positivity for SP263 should be further investigated.
Gesehen am 18.03.2024